MENTAL IMAGERY: METAPHORICAL UNDERSTANDING OF THE CONCEPTUAL SCHEMA “SEARCH FOR FREEDOM” (ON JOHN FOWLES’S NOVEL “THE COLLECTOR”) - Mariya Matkovska (Scientific Journal of Polonia University, 2023)
The aim of the paper is to prove the hypothesis: the conceptual schema “Search for Freedom” verbally embodied into the text is formed on the basis of interpretation of conceptual structures represented by socio-cultural experience. “The Collector” is an existential allegory of the difficulty of living by the dictates of one's own conscience. The author examines the situation in the novel – the relationship between the Few and the Many which is complex and portrayed in clearly existential terms. In “The Collector” Fowles gives us two characters that represent a profound dichotomy of perspectives on life. Miranda quests for knowledge of the Self and attempts to define herself through her relationships with men. This quest for self definition leads to an existential awareness for Miranda. The result proved the fight between Ignorance and Artificiality against Honesty and Freedom. This is a struggle between Jealousy and Envy against the Purity of Creation. It is postulated the idea that the hymn of Freedom, which will never be a part of those who in the name of their particular interests do not see another man, or those for whom everything that is human becomes oddly strange since by enslaving the others they enslave themselves.